Risk Analysis of Oilfield Gathering Station. Issue 1 (2nd October 2018) - Chen, Kun; Liu, Dehuan; Fan, Zhiwen; Chen, Xu; Khan, Faisal
Abstract : Risk analysis and evaluation of oilfield gathering station (OGS) is a challenging task, given that much of the available data are highly uncertain and vague, and many of the mechanisms are complex and difficult to understand. A combinational method of analytic hierarchy process (AHP) and fuzzy comprehensive evaluation (FCE) is proposed in this study to assess hazards in OGS associated with multiple subsystems' failures. The evaluation index system of safety performance in OGS was established, which included tank unit index, pipe unit index, digital monitoring unit index, and other systems. The weight of each index was confirmed through AHP method. Then the AHP and FCE methods were combined to validate the risk levels of representative enterprise S (S‐OGS). The evaluation results show that the evaluation grade of S‐OGS was low risk. This study provides a basis to improve the risk levels of OGS. It is expected that this work may serve as an assistance tool for managers of enterprise in improving the risk levels of oilfield operations. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 71–77, 2019